Antibacterial supramolecular polymers constructed via self-sorting: promoting antibacterial performance and controllable degradation. (19th March 2019) - Yang, Yuchong; Hu, Hao; Chen, Linghui; Bai, Haotian; Wang, Shu; Xu, Jiang-Fei; Zhang, Xi
Abstract : An antibacterial supramolecular polymer is developed that exhibits enhanced antibacterial efficacy and controlled degradability. Abstract : An antibacterial supramolecular polymer is developed that exhibits enhanced antibacterial efficacy and controlled degradability. To this end, a water-soluble bifunctional monomer bearing two naphthalene moieties and a phenylbenzene moiety, as well as a small molecule with antibacterial activity were synthesized. The side-chain antibacterial supramolecular polymer was fabricated through self-sorting of the bifunctional monomer, the small-molecule antibacterial agent, and cucurbit[8]uril. It displayed enhanced antibacterial efficacy against ampicillin-resistant E. coli owing to the local enrichment effect. The controlled degradation of the antibacterial supramolecular polymer could well regulate its antibacterial performance from high to low activity. It is anticipated that this line of research may lead to novel antibacterial supramolecular materials for building degradable antibiotics with enhanced antibacterial efficacy to fight against drug-resistant bacteria.